Attacking scheme against the permutation-based multi-polynomial scheme for pair-wise key establishment in wireless sensor networks - Ai-wen WANG; Tao WEN; Yong ZHANG; Feng-mei ZHU; Di WU (Tongxin xuebao)
An attacking scheme was proposed against the permutation-based multi-polynomial scheme proposed by Guo,et al for pair-wise key establishment in wireless sensor networks.Attacks on polynomials were carried out by constructing a black-box to integrally solve the set of polynomials rather than a single polynomial.The results show that this scheme can break the symmetric polynomials and make the permutation of polynomials lose its function.The proven theorems and instance analysis indicate that the scheme proposed by Guo,et al can’t frustrate the large-scale node capture attack and can’t break the tolerance threshold of polynomials.Therefore,the scheme is insecure.